Upaya Penurunan Kecemasan dengan Pemberian Relaksasi Distraksi - Suhadi Suhadi; Marthunus Judin (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2022)
Anxiety is a common psychological response that can negatively impact a person's well-being if not properly managed. One effective method to alleviate anxiety is through distraction relaxation services, which help divert attention from stressors and promote relaxation. This study explores the effectiveness of distraction relaxation techniques in reducing anxiety levels among individuals experiencing psychological distress. The intervention includes guided relaxation,sensory distraction, and mindfulness-based activities aimed at calming the mind and body. The findings indicate that distraction relaxation services significantly reduce anxiety, improve emotional stability, and enhance overall mental well-being. This study highlights the importance of incorporating relaxation techniques into mental health interventions to support individuals dealing with anxiety.